Relative contributions and capacities of lower extremity muscles to accelerate the body`s center of mass during countermovement jumps - Kipp, K.; Kim, H. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
This study aimed to quantify the contributions and capacities of leg muscles to the body`s center of mass (COM) acceleration during countermovement jumps (CMJ). Ten basketball players performed CMJ while motion capture and ground reaction force data were recorded and used as inputs to a musculoskeletal model. Contributions and capacities to COM acceleration were quantified with three induced acceleration analyses, which showed that the soleus, gastrocnemii, and vastii muscle groups exhibited the largest potential contribution to COM acceleration. Comparisons among analyses suggested that the soleus and vastii muscle group were operating closest to their maximum capacities.